Pengembangan Modul Matematika Berbasis Accelerated Learning pada Materi Himpunan di SMPN 1 Kota Jambi - Nurul Fadila (Journal Evaluation in Education (JEE), 2021)
Pirpose of Study: The purpose of this research is to develop a mathematics module based on accelerated learning for material for class VII SMP which is valid according to experts and to determine the effectiveness of the module. Methodology: This type of research is development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were material validation assessment sheets, module design validation, questionnaires on product trials, student learning outcomes tests, student observation sheets, and student response questionnaires. Main findings: From the results of the analysis, the effectiveness of this module can be seen from the results of observations of student learning activities reaching 86.19% indicating the "very good" category, the results of post-test analysis, namely 85.71% of students achieving the minimum completeness criteria, and the results of the analysis of the questionnaire. student responses show the category "very positive". This means that the module that has been made has shown its effectiveness. Because of this, this module can be used by teachers and junior high school students, especially in learning the Association in Class VII. Research novelty: This research has an update on the variables studied, namely the effectiveness of the accelerated learning-based mathematics module for class VII SMP set material which has never been done by previous researchers.